Impact of rheumatoid arthritis functional status on oral and periodontal health in a multi-ethnic population - Nik-Madihah Nik-Azis,; Fazalina Mohd Fadzilah,; Mohd Shahrir Mohamed Said,; Badiah Baharin,; Nurulhuda Mohd, (Penerbit Universiti Kebangsaan Malaysia, 2019)
Periodontal disease (PD) has both been associated with the pathogenesis of Rheumatoid Arthritis (RA) and is also a comorbidity of RA. The aim of this study was to investigate the impact of the functional status of RA on oral and periodontal health in a multi-ethnic population. This is a hospital-based, multi-ethnic, observational study. Duration of illness, Disease Activity Score (DAS28), seropositivity and other rheumatological parameters were obtained from the records of RA patients attending the Rheumatology Clinic. Oral health examination was conducted on the subjects. Their functional status was assessed using the Health Assessment Questionnaire (HAQ) which includes categories in ‘dressing’, ‘rising’, ‘eating’, ‘walking’, ‘hygiene’, ‘reach’, ‘grip’ and ‘usual activities’. Data were analysed using ANOVA or Kruskal-Wallis test and Pearson’s Correlation or Spearman’s Rank Correlation Test. The 63 RA patients recruited had a mean disease duration of 10.7 ± 9.85 years with a mean of 19.9 teeth (± 7.18). The severity of PD worsens the longer the patients were suffering from RA (p=0.028). A high frequency (70%) of PD with 27% moderate and 27% severe, was observed. A significant association (p=0.035) was found between the ‘eating’ category of the HAQ and the average periodontal pocket depth. This study shows that there is a higher prevalence and severity of PD among RA patients in the selected population. The impact of functional status on periodontal health is mostly in the ‘eating’ category of the HAQ where patients reporting a disability in eating had higher average periodontal pocket depth.